Firms Plunge into the Sea. Marine Biotechnology Industry, a First Investigation - Greco, Gaia R.; Cinquegrani, Marco (Frontiers in Marine Science, 2016)
Marine biology made in the last four decades giant leaps. Several scientific and technological breakthroughs shaped research in the marine environment. Thanks to the revelation of the enormous width and complexity of sea life, marine biotechnology began a fast path of development that involved both the public and the private domain. Although there exist some studies on the dimensions and the evolution of the industry, few and scattered is the knowledge about the firms and the dynamics that characterize the sector. The authors carry out a first investigation of the private organizations that belong to blue biotechnology through the construction of an “ad hoc” sample of firms. It is analyzed the geographical and temporal distribution, the products and services offered and the markets served.